A Post-Neoliberal Era in Latin America? Revisiting Cultural Paradigms - Gómez Michel, Gerardo; López, Magdalena; Nehring, Daniel (Bristol University Press, 2019)
The failure of a number of programmes and ongoing conflicts between neoliberal and post-neoliberal forces have resulted in growing social instability in Latin America. This book examines cultural responses to this instability. It looks at a wide range of cultural forms, such as literature, underground cinema, street fairs and self-help books to explore how Latin Americans construct subjectivities, build communities and make meaning in their everyday lives during a profound crisis of the social. In this context, the book emphasises the role which neoliberal and post-neoliberal narratives of self and social relationships may come to play in popular culture and everyday experience.